2017
DOI: 10.1007/s10389-017-0801-8
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of population Health Checks: have the NHS Health Checks been unfairly maligned?

Abstract: AimThe English NHS currently has a policy of providing Health Checks to all 40–74 year olds. Administered in primary care, they aim to identify patients at risk of a range of diseases, including diabetes and heart disease, and facilitate care. This study is the first to use observed data on the effectiveness of the Checks to consider whether they represent a cost-effective use of limited NHS resources.Subject and methodsUsing a publicly available evaluation tool we conducted an analysis of the Checks to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Overall, our results suggest a lower health and economic impact than some of the early evidence, and are more consistent with the more modest gains reported by Mytton et al 26 and Hinde et al 8 A direct comparison of these modelling exercises is unfortunately not feasible because the scenarios are not directly comparable, the geographies are different and the modelling methods differ substantially.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, our results suggest a lower health and economic impact than some of the early evidence, and are more consistent with the more modest gains reported by Mytton et al 26 and Hinde et al 8 A direct comparison of these modelling exercises is unfortunately not feasible because the scenarios are not directly comparable, the geographies are different and the modelling methods differ substantially.…”
Section: Discussionsupporting
confidence: 87%
“…In the economic models, lower than anticipated coverage, for example, would merely reduce aggregated costs and aggregated health gains, without affecting the cost per QALY estimates. 7,40 Like other interventions (bariatric surgery, for instance) 41 and some pharmaceuticals (which might be subjected to a 'budget impact test'), 42,43 it seems NHS Health Checks may thus be simultaneously costeffective and unaffordable. 40 A pragmatic response might be to focus attention on targeting the distribution of NHS Health Checks towards those who would benefit most, and/or towards reducing health inequalities.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…7,40 Like other interventions (bariatric surgery, for instance) 41 and some pharmaceuticals (which might be subjected to a 'budget impact test'), 42,43 it seems NHS Health Checks may thus be simultaneously costeffective and unaffordable. 40 A pragmatic response might be to focus attention on targeting the distribution of NHS Health Checks towards those who would benefit most, and/or towards reducing health inequalities. The finding that coverage (the proportion of the eligible population who have attended an NHS Health Check) among those in the most deprived areas was higher than average, despite uptake (the proportion of those invited who have attended an NHS Health Check) among those groups being lower (and the findings from the study by Attwood et al in which the direction of association between sociodemographic characteristics and uptake was reversed after adjusting for GP practice), 34 suggests that this is already happening to some degree.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…30,36,38,43,44 in terms of lifestyle advice provided as part of the NHS Health Check, some studies reported benefits, some reported no benefits and some reported mixed results. 34,[44][45][46][47][48][49] Peer reView satisfied with the lifestyle advice and some were not. 34,35,45,47,49 Some participants found the lifestyle advice non-personalised, were confused about how it was communicated or were confused about the follow-ups.…”
Section: Statistical Analysesmentioning
confidence: 99%